Phase‐Selective Synthesis of Ultrathin FeTe Nanoplates by Controllable Fe/Te Atom Ratio in the Growth Atmosphere. Issue 33 (16th July 2021) - Zhang, Hongmei; Li, Qiuqiu; Hossain, Mongur; Li, Bo; Chen, Keqiu; Huang, Ziwei; Yang, Xiangdong; Dang, Weiqi; Shu, Weining; Wang, Di; Li, Bailing; Xu, Weiting; et al.
Abstract: Phase controllable synthesis of 2D materials is of significance for tuning related electrical, optical, and magnetic properties. Herein, the phase‐controllable synthesis of tetragonal and hexagonal FeTe nanoplates has been realized by a rational control of the Fe/Te ratio in a chemical vapor deposition system. Using density functional theory calculations, it has been revealed that with the change of the Fe/Te ratio, the formation energy of active clusters changes, causing the phase‐controllable synthesis of FeTe nanoplates. The thickness of the obtained FeTe nanoplates can be tuned down to the 2D limit (2.8 nm for tetragonal and 1.4 nm for hexagonal FeTe). X‐ray diffraction pattern, transmission electron microscopy, and high resolution scanning transmission electron microscope analyses exhibit the high crystallinity of the as‐grown FeTe nanoplates. The two kinds of FeTe nanoflakes show metallic behavior and good electrical conductivity, featuring 8.44 × 10 4 S m −1 for 9.8 nm‐thick tetragonal FeTe and 5.45 × 10 4 S m −1 for 7.6 nm‐thick hexagonal FeTe. The study provides an efficient and convenient route for tailoring the phases of FeTe nanoplates, which benefits to study phase‐sensitive properties, and may pave the way for the synthesis of other multiphase 2D nanosheets with controllable phases. Abstract : The phase‐controlled synthesis of FeTe nanosheets has been achieved by tuning the atom ratio of Fe precursor and Te precursor in atmosphere. Tetragonal FeTe nanoplates are easier to be obtained in Fe‐rich conditions, while hexagonal FeTe nanoplates tend to grow in Te‐rich conditions. Density functional theory simulations verify the experimental results theoretically.